Validation of the Turkish version of the knee Osteoarthritis outcome score -child questionnaire - Ahmet Onur Akpolat; Onur Gultekin; Halil Ibrahim Arikan; Ahmet Eren Sen; Bekir Eray Kilinc (Journal of Orthopaedic Surgery and Research)
Abstract Background The present study aims to bridge this gap by evaluating the reliability, construct validity, and discriminatory capacity of the Turkish The Knee Osteoarthritis Outcome Score -Child Questionnaire (KOOS-Child). Methods The questionnaire was translated from English to Turkish by two Turkish speaking orthopedic surgeons. Following consensus, the translated version was retranslated to English by a professional translator. A group of experts compared the original and back translated version and decided on a final adapted questionnaire version The study included 119 participants (61 knee problem patients and 58 control patients) aged 8 to 16 years between July 2020 and January 2025. The patients were asked to fill out the KOOS-Child questionnaire and the Children's Quality of Life Questionnaire, which had previously been validated in Turkish. While the demographic characteristics of the groups (age, gender, body mass index (BMI), amount of sports activity) and KOOS-Child Questionnaire scores were compared between the groups, the internal consistency of both groups was examined. In addition, the construct validity and discrimination capacity of the knee pain group were evaluated. Results When demographic characteristics of the groups were compared, the number of professional athletes in the knee pain group was statistically higher. (p < 0.05) When the KOOS Child Questionnaire scores were compared between the groups, both the subscales and the total score of the knee pain group were low (p < 0.05) It was seen that the knee pain group had high level of internal consistency of other subscales and total scores in both groups, except for the symptoms subscale. In the patient group with knee trauma, it was observed that pain, ADL and quality of life and total scores of the girls were lower than the boys (p < 0.05). Conclusion The Turkish KOOS-Child questionnaire exhibits excellent reliability and validity, serving as a practical tool for assessing pediatric knee health, particularly in capturing pain and functional limitations.